RGD/TAT-functionalized chitosan-graft-PEI-PEG gene nanovector for sustained delivery of NT-3 for potential application in neural regeneration. (May 2018) - Wu, Dongni; Zhang, Yongnu; Xu, Xiaoting; Guo, Ting; Xie, Deming; Zhu, Rong; Chen, Shengfeng; Ramakrishna, Seeram; He, Liumin
Graphical abstract: Abstract: In this study, we prepared a multifunctional gene delivery nanovector containing a chitosan (CS) backbone and polyethylenimine (PEI) arms with arginine-glycine-aspartate (RGD)/twin-arginine translocation (TAT) conjugated via polyethylene glycol (PEG). Branched PEI, with a molecular weight of 2000 Da, was used to achieve a balance between biocompatibility and transfection efficiency, whereas RGD/TAT peptides were conjugated for enhanced targeting ability and cellular uptake. Synthesis of the copolymers was confirmed by characterizing the chemical structure with 1 H nuclear magnetic resonance and Fourier Transform Infrared Spectroscopy (FTIR). The nanovector was biocompatible with cells and showed excellent capability for DNA condensation; the resulting complexes with DNA were well-formed, and possessed small particle size and reasonable positive charge. Higher gene transfection efficiency, compared to that achieved with PEI (25 kDa), was confirmed in tumor (HeLa cells) and normal cells (293T and NIH 3T3 cells). More importantly, the cells transfected with the chitosan- graft -PEI-PEG/pCMV-EGFP-Ntf3 complex produced sustained neurotrophin-3 with a linear increase in cumulative concentration, which induced neuronal differentiation of neural stem cell and promoted neurite outgrowth. These findings suggested that our multifunctional copolymers might be ideal nanovectors for engineering cells via gene transfection, and could potentially be applied in tumor therapy and regenerative medicine. Statement of Significance: We successfully prepared a multifunctional gene delivery nanovector containing branched PEI with a molecular weight of 2000 Da to balance between biocompatibility and transfection efficiency, and RGD/TAT peptides for enhanced targeting ability and cellular uptake. The well-formed CPPP/DNA complexes of small particle size and reasonable positive charges potentially enhanced gene transfection in both tumor and normal cells. More importantly, the CPPP/pCMV-EGFP-Ntf3 complex-transfected 293T cells could produce sustained NT-3 with a constant ratio, which induced neuron differentiation of NSC and promoted neurite outgrowth. Therefore, our study provided an effective strategy for producing neurotrophins by engineering cells with gene delivery, which deserved wide investigation and potential application in regenerative medicine.